2015
DOI: 10.1111/jace.13857
|View full text |Cite
|
Sign up to set email alerts
|

Laser Desorption Ionisation Time‐of‐Flight Mass Spectrometry of Chalcogenide Glasses from (GeSe2)100−x(Sb2Se3)x System

Abstract: Laser Desorption Ionization Time‐of‐Flight Mass Spectrometry (LDI TOFMS) was used to characterize chalcogenide glasses from pseudobinary (GeSe2)100−x(Sb2Se3)x system, where x = 5–60, aiming description of their partial structure through the analysis of the plasma formed due to interaction of pulsed laser beam with studied glasses. The plasma contains positively or negatively charged clusters; their stoichiometry was determined as Sec− (c = 2–3), Sb+, Se2+, and Sb3+; binary GeSec+, SbSec+/− (c = 1–2), SbbSec+ (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…are identical). 27 Contrary, the clusters originating from quaternary Ge-Sb-Se-Te thin films were mostly different from those generated from the ternary Ge-Sb-Te system. 32 For example, only three species are common (Ge + , Sb 2 Te + , and Sb 3 Te + ).…”
Section: La Tof-ms Of Ge-sb-se-te Thin Films With Different Se:te Ratiomentioning
confidence: 69%
See 2 more Smart Citations
“…are identical). 27 Contrary, the clusters originating from quaternary Ge-Sb-Se-Te thin films were mostly different from those generated from the ternary Ge-Sb-Te system. 32 For example, only three species are common (Ge + , Sb 2 Te + , and Sb 3 Te + ).…”
Section: La Tof-ms Of Ge-sb-se-te Thin Films With Different Se:te Ratiomentioning
confidence: 69%
“…When comparing the stoichiometry of the clusters obtained from Ge-Sb-Se-Te thin films to those observed from ternary Ge-Sb-Se glasses, 27 it was found that (i) A lower number of clusters is formed. Furthermore, for Te doped thin films, it is demonstrated that the formation of binary and ternary clusters is diminished.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that irradiation of amorphous chalcogenides – in their bulk as well as thin film forms – with a pulsed laser produces many clusters via laser ablation processes, as confirmed through time-of-flight mass spectrometry. This technique can be used to elucidate the structural fragments present in the plasma generated during the interaction of high energy laser pulses with chalcogenide glasses 2527 . However, mass spectrometric study of Ge-Bi-Se materials has not yet been reported, and therefore it is carried out here.…”
Section: Introductionmentioning
confidence: 99%